Difficult Ventilation After Successful Intubation in the Emergency Setting due to a Ball Valve Clot. Issue 10 (15th May 2016) - Liberman, Justin S.; Weigel, Wade; Neal, Joseph M.
Abstract : The inability to ventilate a patient after successful intubation is a rare but emergent situation and may be caused by obstruction of the endotracheal tube, bilateral tension pneumothorax, esophageal intubation, severe bronchospasm, or mainstem bronchus intubation. We describe an increase in mean airway pressure, inability to ventilate, and loss of cardiac output secondary to a blood clot acting as a ball valve at the end of an endotracheal tube.